Investigating community perspectives on falls prevention information seeking and delivery: Older person perceptions regarding preferences for falls prevention education using a World Cafe approach - Bulsara, C.; Khong, L.; Hill, Keith; Hill, Anne-Marie (John Wiley & Sons Inc, 2016)
Falls among older people are a significant global socioeconomic problem, and older adults have low levels of self-perceived risk and a lack of willingness to take up existing falls prevention strategies. We believe that given the challenges of delivering falls prevention information, meaningful engagement of community members would create solutions based on an understanding of what would work best for that community. A World Cafe community forum sought the opinions of 70 community-dwelling older people about their preferences on how they would best receive and seek falls prevention information that could prevent falls within their age group. Participants evaluated the café as a highly positive experience and felt that learning occurred by way of interaction and “sharing of ideas.” Local communities could develop this participatory approach to engage older people in leading the translation of falls prevention evidence into practice.